ANALISIS KEBUTUHAN PERANCANGAN ULANG APLIKASI MOBILE TEMAN BUMIL MENGGUNAKAN FRAMEWORK SCRUM - Meiliani Kuswandi; Clara Hetty Primasari; Yohanes Priadi Wibisono; Aloysius Bagas Pradipta Irianto (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2021)
Seeing the potential for healthtech startups that continue to emerge in Indonesia, of course companies must continue to create innovations to be able to compete with existing and future competitors, one of which is by doing a revamp or a process to change the appearance and user journey. As was done by one of the healthtech startup companies, namely PT. Global Urban Essentials in one of its products, namely the Teman Bumil application. This research was conducted to redesign the display and user journey in the Teman pregnant woman application. The design method used was the Scrum framework. The Scrum stages carried out are the first meeting, sprint planning meeting, sprint, sprint review meeting and sprint retrospective meeting. Data collection was carried out by studying documentation, observation, and interviews. Then the data were analyzed using the Miles and Huberman model with the stages of data reduction, data presentation, and conclusions. Through this research, it is known that the redesign was carried out to change the appearance and improve the experience by shortening the flow of application use, as well as the application design documentation process using the product requirements document guide which consists of three main parts, namely user requirements, interface pages, and flowcharts.